Dinamika Hukum dan Teknologi: Antara Inovasi dan Kepastian Hukum dalam Mewujudkan Ekosistem Digital yang Berkeadilan - Gilang Rizki Aji Putra (UIN Jakarta, 2020)
The relationship between law and technology is paradoxical; while technological advancement drives innovation and societal progress, its rapid pace creates uncertainty and regulatory challenges. This article examines the friction between innovation and legal certainty in Indonesia’s digital governance. Using normative legal research with conceptual and comparative approaches, the study finds that Indonesian law faces a persistent pacing problem, lagging behind technological developments. Key tensions emerge in fintech, artificial intelligence, and platform economies, where rigid regulations hinder experimentation and create risks for innovation and consumer protection. Adaptive legal frameworks are therefore essential. Keywords: Technological Innovation, Legal Certainty, Pacing Problem, Platform Economy, Adaptive Law